2020
DOI: 10.1007/s10499-020-00536-x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of soy lecithin–enriched Artemia on growth and survival of the early stages of green tiger shrimp (Penaeus semisulcatus)

Abstract: The lecithin (LST) requirements for young and adult crustaceans have been investigated, and little information is available for early life stages. Therefore, our study aimed to determine the best Artemia enrichment levels with soy lecithin as a means of maintaining better survival, growth rate, and total length during the early stages (mysis 1 to post-larva 7) of the green tiger shrimp, Penaeus semisulcatus. Artemia enrichment at five different lecithin levels (0, 1, 2, 3, and 4% soy lecithin) was carried out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Gong et al (2004) documented that the supplementation of phospholipids increased the osmoregulatory capacity of the shrimps. Furthermore, soy-lecithin is not only a source of energy but also has a considerable quantity of essential fatty acids, phosphorus and vitamins that would help to stabilise cell membranes and improve digestion, absorption and consumption of nutrients, especially lipids (Yilmaz, 2020). Similarly, Sanchez et al (2014) found that P. vannamei fed 4% soy-lecithin grew faster than those fed 1% soy-lecithin, who suggested that this beneficial effect was due to increased lipid deposition and energy availability for growth, which might be attributed to increased transport and mobilisation of lipids from the hepatopancreas to the haemolymph and other tissues.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gong et al (2004) documented that the supplementation of phospholipids increased the osmoregulatory capacity of the shrimps. Furthermore, soy-lecithin is not only a source of energy but also has a considerable quantity of essential fatty acids, phosphorus and vitamins that would help to stabilise cell membranes and improve digestion, absorption and consumption of nutrients, especially lipids (Yilmaz, 2020). Similarly, Sanchez et al (2014) found that P. vannamei fed 4% soy-lecithin grew faster than those fed 1% soy-lecithin, who suggested that this beneficial effect was due to increased lipid deposition and energy availability for growth, which might be attributed to increased transport and mobilisation of lipids from the hepatopancreas to the haemolymph and other tissues.…”
Section: Resultsmentioning
confidence: 99%
“…The performance is better with high dietary phospholipids than diets high in polyunsaturated fatty acids. Phospholipids, in general, are rich in soy-lecithin (phosphatidylcholine) and have been shown to improve the growth of various penaeid shrimps such as P. japonicus (Kontara et al, 1997), P. monodon (Khan et al, 2018), P. semisulcatus (Yilmaz, 2020) and P. vannamei (Yan et al, 2020). However, the optimised values varied in the earlier reports for aquatic species and were in the range of 1-3% in crustaceans and 1.5-12% for fish (NRC, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Lecithin is composed of phospholipids and has a main role in sh liver also it is a career for fatty acids as an emulsi er in biological absorption systems (Gisbert et al 2005). Moreover, lecithin has phosphorus, vitamins, essential fatty acids, energy resources also can enhance the fat digestion and absorption and improve cell membrane's function (Yilmaz 2020). Lecithin can affect the growth performance of sh because of the several of antioxidant capacity and the fatty acid pro le of feed (Yilmaz 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, lecithin has phosphorus, vitamins, essential fatty acids, energy resources also can enhance the fat digestion and absorption and improve cell membrane's function (Yilmaz 2020). Lecithin can affect the growth performance of sh because of the several of antioxidant capacity and the fatty acid pro le of feed (Yilmaz 2020). According to the Tan et al (2022) the soybean lecithin improved the structure of intestine, increased muscular thickness and mucosal fold height of the mid-intestinal tissue and diet enhanced the transcriptional level of fatty acid activation-related genes (acsl6 and acsbg2) of the rock bream larvae.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation